Thoracolumbar spinal neurenteric cyst with tethered cord syndrome and extreme cervical lordosis in a child: A case report and literature review. Issue 16 (April 2018) - Lan, Zhi Gang; Richard, Seidu A.; Lei, Chuanfen; Huang, Siqing
Abstract: Rationale: Neurenteric cysts, are rare benign tumors of the central nervous system that are mostly located in the spinal cord and predominantly seen in male children although adult form of the disorder also occurs. The etiology and treatment of this disorder is still a matter of debate. Our case further throws more light on the pathogenesis and treatment of this disorder. Patient concerns: A 4-year-old boy presented with 5-month history of cervical lordosis and bilateral lower extremity pain that progressed to his abdomen and upper body. The pain was general, recurrent, non-persistent and progressive in nature with no paralysis. The pain was aggravated by trunk stretching and relieved when he assumed opisthotonos position so he preferred sleeping in this position at night. Diagnoses: Magnetic resonance imaging (MRI) revealed a cystic lesion at the thoracolumbar spine with tethering of spinal cord and cervical lordosis. Interventions: He was operated on successfully and the cervical lordosis and pain resolved. Outcomes: The child recovered well with no tumor recurrence and massive improvement of his life. Lessons: The gold standard treatment for this disorder is surgery although the precise surgical approach is still a matter of debate. We are of the view that surgical approach should be individualized and aim at total excision of the cyst.